question types as predictors of academic performance in English Language among secondary school students in Lagos main land, Lagos State, Nigeria (2016)
This study investigated teacher question types i.e. open ended question types and close ended question types otherwise known as divergence question types and convergence question types (evaluation, inference, problem solving, comparison, application and knowledge) as predictor of academic performance among senior secondary school students in selected local government area of Lagos state. The participants were two-hundred and fifty. Three research questions were raised and tested using Pearson Product Moment Correlation and Multiple Regression Analysis. An English language achievement test consisting of open ended question types and close ended question types was used to collect data. The findings revealed that there was significant positive relationships between inference question type (r = 0.238, p < 0.05); problem solving question type (r = 0.229, p< 0.05); knowledge question type (r = 0.476, p< 0.05) while there was no significant relationship between evaluative question type (r = 0.118, p<0.05), comparison question type (r = 0.152, p < 0.05), application question type (r = 0.019, p < 0.05) on academic performance in English language among the participants. The result shows a coefficient of multiple correlations (R) of 0.996 and a multiple R square of 0.992. This means that six variables jointly accounted for 99.2% of the variance in the academic performance of students in English language. The independent variables made positive relative contribution to academic performance in English language in the following order: application question types ( = .396, t= 67.721, p < 0.05) followed by comparison question type ( = .365, t= 54.764, p<0.05), followed by inference question types ( = .296, t= 49.304, p<0.05) followed by problem solving question type ( = .273, t= 41.326, p<0.05) followed by evaluation question type ( = .237, t= 39.621, p<0.05) and finally knowledge question type ( = .230, t= 39.531, p<0.05) in that order. Based on this the teachers should be allowed to attend in-service training on tests construction and the different types of questions so as to avoid setting questions that are based on lower order of thinking